RE-THINKING MANDATORY AUDITOR ROTATION: A COMPARATIVE ANALYSIS - Schoeman, Werner (Obiter, 2023)
Since formation of the European Union, there has been a worldwide upsurge in regulation of the auditing profession, which has included mandatory auditor rotation and this has also found its way into South African company law, regardless of the many arguments against it. The number of corporate scandals or company failures justifies an evaluation of the effectiveness of such regulation and a re-thinking of the concept of auditor rotation. Revisiting the arguments against and in favour of mandatory auditor rotation confirms the rational arguments against mandatory auditor rotation. These arguments are opposed to the main reason for its implementation – namely, that rotation will serve as a publicly acceptable band-aid on damaged investor confidence. Overshadowed by corporate scandals, regulators face constant pressure to enhance auditors’ independence and to amend and improve regulations. To inform the South African stance, developments regarding auditor rotation in Germany and Australia are examined. An assessment of the significance of mandatory auditor rotation in the current corporate-law environment reveals that Steinhoff (Steinhoff International Holdings N.V.) failed in 2018, despite the fact that auditor-rotation legislation was in place. This supports arguments against auditor rotation and suggests that South Africa too hastily followed international trends. Mandatory auditor rotation regulations in South Africa also discourage potential candidates from entering the auditing work environment. It is submitted that the current provisions do not contribute effectively to auditor independence and are merely desperate attempts to curb the public’s lack of confidence in the auditing profession. Section 92 of the Companies Act 71 of 2008, dealing with mandatory auditor rotation, should therefore be repealed.